MECHANISM OF FORMING OF THE MIXTURE CHARACTERISTICS IN THE PERIOD OF STIRRING OF ITS COMPONENTS - A. P. Melnikov; M. A. Sajkov; D. M. Golub (Литьë и металлургия)
The process of blending of components in mixture has compound complex of physical and chemical phenomenon, control of which is possible by the way of deep study of the mechanism of the characteristics forming in mixture